More recent advances in (hyper)graph partitioning - Çatalyürek, Ümit; Devine, Karen; Fonseca Faraj, Marcelo; Gottesbüren, Lars; Heuer, Tobias; Meyerhenke, Henning; Sanders, Peter; Schlag, Sebastian; Schulz, Christian; Seemaier, Daniel; Wagner, Dorothea (ACM computing surveys, 2023)
In recent years, significant advances have been made in the design and evaluation of balanced (hyper)graph partitioning algorithms. We survey trends of the past decade in practical algorithms for balanced (hyper)graph partitioning together with future research directions. Our work serves as an update to a previous survey on the topic [29]. In particular, the survey extends the previous survey by also covering hypergraph partitioning and has an additional focus on parallel algorithms.
Gesehen am 05.06.2023